Supplementation of Multistrain Probiotics Improves Milk Production, Blood Metabolites, Digestibility, and Rectal Microbiota during the Prepartum and Early Lactation Stages in Crossbred Cows - Mohamed S. Ayyat; Usama M. Abdel Monem; Gamal Abdel-Rahman; Adel Ibrahim Hussein; Hamdy A. El-Nagar; Wael M. Wafa; Samir Mahgoub; Adham A. Al-Sagheer (Veterinary Medicine International)
The current study aimed to study the effects of administration with a multistrain probiotic formulation (MPF) initiated from the prepartum stage on lactation performance, digestibility, rectal microbiota, and blood metabolites of postpartum dairy cows. A total of 30 multiparous crossbred (Holstein Friesian × Balady) dairy cows were randomized into three groups: control (no MPF supplementation), MPF1 (0.5 g MPF/cow/d), and MPF2 (1 g MPF/cow/d). The administration of MPF started 28 days before calving and continued for 84 days after. The results revealed that cows in the MPFI and MPF2 groups had higher milk production, 3.5% FCM, and ECM than those in the control group. The MPF-supplemented cows had significantly greater milk energy output, DMI, and yields of solids-not-fat, lactose, total solids, ash, fat, and protein. The MPF supplementation significantly enhanced feed conversion and significantly interacted with milk solids-not-fat, lactose, total solids, and protein. Hematological indicators did not significantly alter between the MPF and control groups. However, cows receiving MPF supplements had higher levels of Hct. Serum biochemical measurements showed lower serum concentrations of LDL, total cholesterol, and VLDL in MPF-fed cows than in the control group. The digestibility of organic and dry matter tended to be higher in MPF-supplemented cows. The populations of lactobacillus, bacillus, and total bacterial count increased due to MPF administration, while the count of Clostridium, Salmonella, E. coli, and coliforms decreased in MPF-fed cows. In summary, administering MPF during late gestation and early lactation period improved milk production, fecal microbial composition, and overall health of dairy cows.